PENGARUH DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN BAGIAN KONTRUKSI PADA PT. RIFANSI DWI PUTRA DURI - ,Arwinence Pramadewi, Shofi Dhia Karunia , Zulfadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
Every Company wants its members to participate in achieving targets. To achieve this target, the company must be abel to improve the performance of its employees by increasing employee discipline and providing compensation to increase job satisfaction. This study aims to determine the effect of work discipline and compensation on the performance of construction employees at PT. Rifansi Dwi Putra. This research was conducted in Duri City. The population in this study were 500 construction employees. The sampling technique that has been chosen is the Purposive Sampling method with 84 samples. The data analysis tool used in this study was Multiple Linear Regression Analysis with the help of the SPSS 23 program. The results showed that: 1) Work Discipline Variables have a positive and significant effect on employee performance, 2) Compensation Variables have a positive and significant effect on employee performance, 3 ) Work Discipline and Compensation variables have a joint effect on employee performance.Keywords: Discipline, Compensation, Employee performance